2014
DOI: 10.1039/c3fo60683j
|View full text |Cite
|
Sign up to set email alerts
|

A new “functional” pasta containing tartary buckwheat sprouts as an ingredient improves the oxidative status and normalizes some blood pressure parameters in spontaneously hypertensive rats

Abstract: Epidemiological studies have reported that some foods, particularly those rich in (poly)phenols, may reduce cardiovascular risk and metabolic disorders such as hypertension. Buckwheat sprouts have been suggested as a new raw material for the production of functional foods due to their high content of healthy compounds such as rutin and quercetin. The aim of this paper is to evaluate the biological hypotensive and antioxidant responses of pasta containing tartary buckwheat sprouts (TBSP) on spontaneously hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…Tartary buckwheat seeds are an important resource that can be processed into various food products such as tea, noodles and pastries (Ma et al, 2013;Merendino et al, 2014;Qin et al, 2013). As seeds mature, they undergo changes in terms of shape, colour and dry weight (DW).…”
Section: Introductionmentioning
confidence: 99%
“…Tartary buckwheat seeds are an important resource that can be processed into various food products such as tea, noodles and pastries (Ma et al, 2013;Merendino et al, 2014;Qin et al, 2013). As seeds mature, they undergo changes in terms of shape, colour and dry weight (DW).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is more effective than verapamil in the antihypertensive action, and this more effective action of quercetin is mediated through reduction of body fluid volume (diuresis). 36 Antihypertensive activity of quercetin has also been observed in spontaneously hypertensive rats, 37 in which quercetin diminishes blood pressure by attenuating the noradrenaline-induced vascular contraction in a perfused mesenteric vascular bed 38 via elevation of the sensitivity to parasympathetic baroreflex 39 and diminution of mRNA expression and activity of angiotensin-converting enzyme. 40 Oral administration of quercetin is also effective as an antihypertensive treatment in hypertensive rats developed by NaCl-induced volume expansion.…”
Section: Antihypertensive Action Of Quercetinmentioning
confidence: 99%
“…Buckwheat sprouts are becoming popular as a health‐promoting food product . Lin et al reported that sprouting greatly improved the nutrient contents of buckwheat, especially total polyphenolics, rutin, quercetin, l ‐ascorbic acid and γ‐aminobutyric acid (GABA) and related appreciable hypolipidemic bioactivity.…”
Section: Other Buckwheat Productsmentioning
confidence: 99%